Hello,
f(x) has as inverse f^(-1)(x)
and (fof^(-1))(x)=(f^(-1)of)(x)= x (the neutral function)
so h(f(x))=x
The formula for the light bend would be n1*sin i= n2 * sin r
If you use "sin (90-x)= cos x" principle, you can change the sin in the equation into
n1*sin i= n2 * sin r
n1 * cos a= n2 * cos b
n2/n1= cos a/ cos b
Assuming the n constant is the ratio of the glass compared to water then the answer would be: cos a/ cos b
Answer : 12312
Step-by-step explanation : According to BODMAS, Addition (+) comes first
Hence -- 9 + 19 + 12 + 12323 = 12363
12363 - 12 - 39 = 12363 - 51
= 12312
I would be able to but i left my maths book at school and that has the explanation in, sorry :(
You can ask questions on here and people will answer them the best they can